The Superstructure of Public Service Advertisements on Plastic Waste - Putu Ratna Ariasih; Gusti Made Sutjaja; Ni Wayan Kasni (RETORIKA: Jurnal Ilmu Bahasa, 2020)
This study concerns the ad texts from the perspective of discourse structure. At a specific layer, it reveals the superstructure of a five-type public service advertisement text discourse taken from Youtube. The five advertisements in question are â€œDiet Kantong Plastikâ€, â€œPolusi Plastik Multimedia SMKN 1 Surabaya 2018/2019â€, â€œKampanye Sosial Menguragi Sampah Plastikâ€, â€œKurangi Sampah Plastikâ€ and â€œPolusi Sampah Plastikâ€. Achieving this goal was done by making use of a qualitative research design. The data were collected through several procedures namely finding, downloading, filtering, taking notes and researching the data to discover the text superstructure. Data were analyzed using padan method, or identity method. Then the results of data analysis are presented in the form of a description. The study addresses the issue of discourse structure with the superstructure (Dijk, 1980) theory approach. The results of the data analysis showed that each adver- tisement had four sequences of structures, namely introduction, body, closing and conclusion. These four com- ponents are the ones that form the fifth superstructure of the public service advertisements reviewed in this paper. By chance a service advertisement is indeed of many analysable aspects. The present study is only re- stricted to plastic trash community service ads on Youtube. However, public service announcements or adver- tisements can also be obtained from other electronic media such as TV or radio and from the print media. For the futher studies, it is necessary to explore the community service advertisements on plastic waste that are displayed through these media.